Faculty Perceptions of Feedback in Objective Structured Clinical Examinations (OSCEs): Feedback in Objective Structured Clinical Examinations - Abdullah, Zainab; Kashif, Lubna; Khan, Marina; Fatima, Syeda Sanaa; Tauqir, Asya; Manzoor, Saima (Pakistan Journal of Health Sciences, 2026)
Objective Structured Clinical Examinations (OSCEs) are widely used to assess clinical competence in health professions education. Although OSCEs are considered reliable and objective, their educational impact largely depends on the quality of feedback provided. Objective: To evaluate the faculty perceptions regarding OSCE feedback practices in local institutional settings. Methods: This descriptive cross-sectional study was conducted at Bashir Institute of Health Sciences, Islamabad, from January 2025 to June 2025. A total of 110 faculty members involved in OSCE conduction and evaluation were recruited using non-probability consecutive sampling. Data were collected using a structured, self-administered questionnaire developed using expert opinion and feedback from the literature, addressing demographic characteristics, perceptions of OSCE feedback, preferred feedback practices, and perceived barriers. Data were analyzed using SPSS version 26.0 with descriptive statistics and the Pearson Chi-square test. Results: The mean age of participants was 43.37 ± 8.17 years, with females comprising 52.7% of the sample. Most faculty agreed that feedback is essential for student learning (60.0%) and improves clinical competence (84.5%). Immediate feedback was preferred by 52.7% of participants, while written (33.6%) and one-to-one (31.8%) methods were most favored. Lack of formal training (57.3%), large student numbers (43.6%), and stressful OSCE environments (42.7%) were identified as key barriers. No significant associations were observed between overall perception of feedback and faculty characteristics. Conclusions: Faculty members value feedback in OSCEs but face practical challenges that limit its effective delivery. Focused faculty development and institutional support are needed to enhance feedback quality.